Reproducing empire : race, sex, science, and U.S. imperialism in Puerto Rico - Briggs, Laura, 1964- (Berkeley : University of California Press, 2002)
Annotation Original and compelling, Laura Briggs'sReproducing Empireshows how, for both Puerto Ricans and North Americans, ideologies of sexuality, reproduction, and gender have shaped relations between the island and the mainland. From science to public policy, the "culture of poverty" to overpopulation, feminism to Puerto Rican nationalism, this book uncovers the persistence of concerns about motherhood, prostitution, and family in shaping the beliefs and practices of virtually every player in the twentieth-century drama of Puerto Rican colonialism. In this way, it sheds light on the legacies haunting contemporary debates over globalization. Puerto Rico is a perfect lens through which to examine colonialism and globalization because for the past century it has been where the United States has expressed and fine-tuned its attitudes toward its own expansionism. Puerto Rico's history holds no simple lessons for present-day debate over globalization but does unearth some of its history. Reproducing Empiresuggests that interventionist discourses of rescue, family, and sexuality fueled U.S. imperial projects and organized American colonialism. Through the politics, biology, and medicine of eugenics, prostitution, and birth control, the United States has justified its presence in the territory's politics and society. Briggs makes an innovative contribution to Puerto Rican and U.S. history, effectively arguing that gender has been crucial to the relationship between the United States and Puerto Rico, and more broadly, to U.S. expansion elsewhere
EPILOGUE: Ghosts, Cyborgs, and Why Puerto Rico Is the Most Important Place in the WorldNotes; Bibliography; Index
Includes bibliographical references (pages 243-266) and index.
Print version record.
English.
JSTOR
Keywords: Birth control -- Puerto Rico -- History; Sterilization (Birth control) -- Puerto Rico -- History; Prostitution -- Puerto Rico -- History; Prostitution -- History; Puerto Ricans -- United States; United States -- Relations -- Puerto Rico; Puerto Rico -- Relations -- United States; Family planning services; Medical policy; Prostitution; Sterilization; Family Planning Services; Colonialism; Health Policy; Sex Work; Sterilization; Contraception -- history; Puerto Rico; Régulation des naissances -- Porto Rico -- Histoire; Stérilisation (Régulation des naissances) -- Porto Rico -- Histoire; Porto Rico -- Relations -- États-Unis.; Services de planification familiale; Politique sanitaire; Prostitution; Stérilisation.; prostitution; sterilization; SOCIAL SCIENCE -- Abortion & Birth Control; HISTORY -- United States -- General; Sterilization; Medical policy; Family planning services; Birth control; Prostitution; Puerto Ricans; International relations; Sterilization (Birth control); Puerto Rico; United States; 20th century; american colonialism; anthropology; culture of poverty; expansionism; feminism; gender issues; gender studies; globalization; international relations; island life; modern history; nationalism; north america; overpopulation; political perspective; postcolonial; public policy; puerto rico; race relations; racial issues